PENERAPAN MODEL LEARNING CYCLE 5E BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS IV SDN 1 KALIMANAH WETAN PADA MATA PELAJARAN IPAS - Oktavriano, Rizki Alkafia; Muslim, Aji Heru (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to improve the motivation and learning achievement of fourth-grade students at SD Negeri 1 Kalimanah Wetan through the implementation of the Learning Cycle 5E model assisted by Wordwall media in Science (IPAS) lessons. The study was motivated by students’ low learning motivation and low mastery in cognitive domains. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model. The subjects were 23 students, comprising 11 boys and 12 girls. Data were collected through observation sheets, learning motivation questionnaires, and evaluation sheets. The results showed an increase in both motivation and learning achievement. In cycle I, 67.4% of students demonstrated high learning motivation, which increased to 100% in cycle II. Student learning achievement also improved, with an average score of 67.30 and 69.57% mastery in cycle I, rising to 75.54 with 82.61% mastery in cycle II. It can be concluded that the implementation of the Learning Cycle 5E model assisted by Wordwall effectively enhances both motivation and learning achievement in Science lessons for fourth-grade students.